Talas-Talasan (Araceae) Sumber Pangan Lokal Di Kawasan Karst Kecamatan Pracimantoro Kabupaten Wonogiri - Jayanti, Endah Dwi; Jumari, J; Wiryani, Erry (Bioma : Berkala Ilmiah Biologi, 2017)
Taros (Araceae) is a group of bulbous plants which are commonly found in Indonesia. Araceae have a high carbohydrate content, so it is potential to be used as a local food source for the community. The purpose of this research was to assess the types and cultivars, cultivation status, and the utilization of Araceae found in the karst area of Pracimantoro District, Wonogiri. The research was held in January to May 2016. Plant sample was taken in six villages, Sumberagung, Gedong, Gebangharjo, Glinggang, Wonodadi and Gambirmanis. The data were analyzed descriptively. The results is, 9 variants of Araceae which belong to 4 species was found in the karst area of Pracimantoro. Cultivation status of Araceae is semi-wild, that is not planted and given specific treatment. The utilization of Araceae in Pracimantoro District generally as food additives, other uses is for medicinal and ornamental plantsÂ Key word: Araceae, Local food resources, Karst area, Pracimantoro.